2017
DOI: 10.1021/acsbiomaterials.7b00072
|View full text |Cite
|
Sign up to set email alerts
|

The Hair Follicle: An Underutilized Source of Cells and Materials for Regenerative Medicine

Abstract: The hair follicle is one of only two structures within the adult body that selectively degenerates and regenerates, making it an intriguing organ to study and use for regenerative medicine. Hair follicles have been shown to influence wound healing, angiogenesis and neurogenesis, and harbor distinct populations of stem cells; this has led to cells from the follicle being used in clinical trials for tendinosis and chronic ulcers. In addition, keratin produced by the follicle in the form of a hair fiber provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 166 publications
(321 reference statements)
0
28
0
Order By: Relevance
“…4D). The presence of these appendages can improve the wound healing process, considering that, in the epithelial compartment of the folicles, there are stem cells that can differentiate into numerous cell types 51 . Furthermore, hair folicles are a source of pro-angiogenic factors, such as VEGF 52 .…”
Section: Discussionmentioning
confidence: 99%
“…4D). The presence of these appendages can improve the wound healing process, considering that, in the epithelial compartment of the folicles, there are stem cells that can differentiate into numerous cell types 51 . Furthermore, hair folicles are a source of pro-angiogenic factors, such as VEGF 52 .…”
Section: Discussionmentioning
confidence: 99%
“…However, because they readily facilitate bone formation [ 35 ], they may not provide a true representation of ectopic or inappropriate bone formation in an in vitro model. Human dermal papilla (DP) cells are specialised mesenchymal cells found at the base of the hair follicle that play a key role in hair growth and cycling [ [36] , [37] , [38] ], and are accordingly unrelated to bone. Curiously, while not being stem cells, human DP cells do have multipotent tendencies in vitro and can differentiate down both osteogenic and adipogenic lineages when grown in specific differentiation medias [ [39] , [40] , [41] ].…”
Section: Introductionmentioning
confidence: 99%
“…19 Beyond the cell types mentioned above, hair follicles contain a number of stem cells at their base that play a role in wound healing. [20][21][22] Si et al found that transfecting hair follicle stem cells with the lncRNA PlncRNA-1 increased their proliferation and differentiation. Treatment of these transfected cells with the TGF-β1 inhibitor LY2109761 decreased these effects, suggesting a role for PlncRNA-1 in the TGF-β1-mediated Wnt/β-catenin signaling cascade.…”
Section: Integumentary Systemmentioning
confidence: 99%
“…Beyond the cell types mentioned above, hair follicles contain a number of stem cells at their base that play a role in wound healing 20‐22 . Si et al found that transfecting hair follicle stem cells with the lncRNA PlncRNA‐1 increased their proliferation and differentiation.…”
Section: Therapeutic Activity Of Lncrna For Tissue Repair and Regenermentioning
confidence: 99%